Studi Hospitality Terhadap Minat Kunjung Ulang Pada Destinasi Wisata Danau Sipin - Wandirah Wandirah (Jurnal Dinamika Manajemen, 2021)
This study aims to determine the interest in revisiting tourists in hospitality studies. This research uses descriptive quantitative method with multiple linear regression analysis tools. The subjects of this study were Jambi University students who had visited Sipin Lake as a tourist destination. The sampling technique used was purposive sampling. The number of samples used in this study amounted to 100 respondents. The results of this study indicate that hospitality partially and simultaneously has a significant effect on the interest in returning tourists